A nanocomposite paste electrode sensor for simultaneous detection of uric acid and bisphenol a using zinc hydroxide nitrate-sodium dodecylsulfate bispyribac - Illyas Md Isa (Tanjung Malim, 2023)
A nanocomposite paste electrode sensor for simultaneous detection of uric acid and bisphenol a using zinc hydroxide nitrate-sodium dodecylsulfate bispyribac by Illyas Md Isa